Answer: D
Step-by-step explanation:
Consider the first equation. Subtract 3x from both sides.
y−3x=−2
Consider the second equation. Subtract x from both sides.
y−2−x=0
Add 2 to both sides. Anything plus zero gives itself.
y−x=2
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.
y−3x=−2,y−x=2
Choose one of the equations and solve it for y by isolating y on the left hand side of the equal sign.
y−3x=−2
Add 3x to both sides of the equation.
y=3x−2
Substitute 3x−2 for y in the other equation, y−x=2.
3x−2−x=2
Add 3x to −x.
2x−2=2
Add 2 to both sides of the equation.
2x=4
Divide both sides by 2.
x=2
Substitute 2 for x in y=3x−2. Because the resulting equation contains only one variable, you can solve for y directly.
y=3×2−2
Multiply 3 times 2.
y=6−2
Add −2 to 6.
y=4
The system is now solved.
y=4,x=2
Answer:
I think is -x + 105/42y
Step-by-step explanation:
2(3/10)x - 5/7y - 4(5/6)y - 2(4/5)x
6/10x - 5/7y - 20/6y - 8/5x
6/10x - 8/5x - 5/7y - 20/6y
6-16/10x - 35+140/42y
-10/10x + 105/42y
-x + 105/42y
The <em>second order</em> polynomial that involves the variable <em>x</em> (border inside the rectangle) and associated to the <em>unshaded</em> area is x² - 62 · x + 232 = 0.
<h3>How to derive an expression for the area of an unshaded region of a rectangle</h3>
The area of a rectangle (<em>A</em>), in square inches, is equal to the product of its width (<em>w</em>), in inches, and its height (<em>h</em>), in inches. According to the figure, we have two <em>proportional</em> rectangles and we need to derive an expression that describes the value of the <em>unshaded</em> area.
If we know that <em>A =</em> 648 in², <em>w =</em> 22 - x and <em>h =</em> 40 - x, then the expression is derived below:
<em>A = w · h</em>
(22 - x) · (40 - x) = 648
40 · (22 - x) - x · (22 - x) = 648
880 - 40 · x - 22 · x + x² = 648
x² - 62 · x + 232 = 0
The <em>second order</em> polynomial that involves the variable <em>x</em> (border inside the rectangle) and associated to the <em>unshaded</em> area is x² - 62 · x + 232 = 0. ![\blacksquare](https://tex.z-dn.net/?f=%5Cblacksquare)
To learn more on polynomials, we kindly invite to check this verified question: brainly.com/question/11536910
Answer:
A= (0,0) and B = (6,3)
We can find the length AB with the following formula:
![d = \sqrt{(x_B -x_A)^2 +(y_B -y_A)^2}](https://tex.z-dn.net/?f=%20d%20%3D%20%5Csqrt%7B%28x_B%20-x_A%29%5E2%20%2B%28y_B%20-y_A%29%5E2%7D)
And replacing we got:
![d = \sqrt{(6-0)^2 +(3-0)^2} = \sqrt{45}= 3\sqrt{5}](https://tex.z-dn.net/?f=%20d%20%3D%20%5Csqrt%7B%286-0%29%5E2%20%2B%283-0%29%5E2%7D%20%3D%20%5Csqrt%7B45%7D%3D%203%5Csqrt%7B5%7D)
So then the length AB would be ![3\sqrt{5}](https://tex.z-dn.net/?f=%203%5Csqrt%7B5%7D)
Step-by-step explanation:
For this case we have the following two points:
A= (0,0) and B = (6,3)
We can find the length AB with the following formula:
![d = \sqrt{(x_B -x_A)^2 +(y_B -y_A)^2}](https://tex.z-dn.net/?f=%20d%20%3D%20%5Csqrt%7B%28x_B%20-x_A%29%5E2%20%2B%28y_B%20-y_A%29%5E2%7D)
And replacing we got:
![d = \sqrt{(6-0)^2 +(3-0)^2} = \sqrt{45}= 3\sqrt{5}](https://tex.z-dn.net/?f=%20d%20%3D%20%5Csqrt%7B%286-0%29%5E2%20%2B%283-0%29%5E2%7D%20%3D%20%5Csqrt%7B45%7D%3D%203%5Csqrt%7B5%7D)
So then the length AB would be ![3\sqrt{5}](https://tex.z-dn.net/?f=%203%5Csqrt%7B5%7D)